Espécies vegetais utilizadas na terapêutica e/ou prevenção da covid-19: revisão integrativa, análise da desinformação na internet e estudo etnodirigido na população de São Luís-Maranhão - FERREIRA, Beatriz Ribeiro (2023)
COVID-19 is an infectious disease caused by the SARS-CoV-2 coronavirus, which emerged in Wuhan, China, at the end of 2019. It quickly spread around the world and was declared a pandemic by the World Health Organization (WHO). The most common symptoms of COVID-19 include fever, dry cough, fatigue and difficulty breathing, and can range from mild to severe. The lack of a specific treatment for the disease has sparked a growing interest in the medicinal properties of plants as possible allies in dealing with the disease. Some plants have been studied for their antiviral, immunomodulatory and anti-inflammatory properties, which could play an important role in preventing and treating symptoms related to COVID-19. Thus, the aim of this study is to carry out a survey of plant species used and/or referred to popularly in the treatment and/or prevention of COVID-19, involving an integrative bibliographic review and an investigation into the dissemination of misinformation on the subject on the internet; as well as to carry out an ethnodirected study with the population of São Luís, Ma. The research began with an integrative review (article 01) in databases of plant species with antiviral and immunomodulatory potential used in the context of Covid-19 according to ethnodirected studies published between 2020 and 2022. Next, an analysis was carried out on search engines (article 02), looking for publications on natural products of plant origin used and/or popularly referred to in the therapy and/or prevention of COVID-19, evaluating the information and comparing it with the literature, in order to verify whether it was fact or fake. Finally, field research was carried out, with an ethnodirected approach (article 03), with 400 individuals being interviewed, 200 from health establishments in São Luís, Maranhão and 200 online from December 2022 to March 2023. In the ethnobotanical study (article 02), the most commonly cited species were Curcuma longa L. (Saffron), Echinacea purpurea (L.) Moench (Echinacea), Rosmarinus officinalis L. (Rosemary) and Zingiber officinale Roscoe (Ginger), Allium sativum L. (Garlic), Eucalyptus globulus Labill. (Eucalyptus), Glycyrrhiza glabra L. (Licorice). (Licorice), Matricaria chamomilla L. (Chamomile), Pimpinella anisum L. (Fennel), Polygonum cuspidatum Siebold & Zucc. and Uncaria tomentosa (Willd.) DC. (Cat's claw), it was analyzed that even with some studies portraying antiviral and/or immunomodulatory effect, there are still no robust studies that prove the proper use in the treatment of COVID-19. In the ethnodirected study (article 03) conducted, the six most cited species were Uncaria tomentosa (Willd.) DC., Plectranthus barbatus Andrews (Boldo), Citrus limon (L.) Osbeck (Lemon), Zingiber officinale Roscoe.(Ginger), Allium sativum L. (Garlic) and Stellaria media (L.) Vill. (Mint). As a final result, the "MEDFlora" database was produced, containing all the plants inventoried and their studies, as well as a booklet to provide health education for this population. These data together encourage the continued validation of the antiviral activity against SARS-CoV-2 of the species through pre-clinical and clinical trials and reinforce the role of ethnobotany as a tool, both in the selection of plant species for Research and Development of new bioproducts, and in the identification of risks and dangers associated with the popular therapeutic use of plants without proven efficacy and safety, encouraging Pharmacovigilance actions in Phytotherapy.